2006
DOI: 10.1007/s10552-005-3637-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends for in situ and Invasive Melanoma in Queensland, Australia, 1982–2002

Abstract: Age-standardised incidence is continuing to increase and this, in combination with a shift to proportionately more in situ lesions, suggests that the stabilisation of mortality rates is due, in large part, to earlier detection. For primary prevention, after a substantial period of sustained effort in Queensland, there is some suggestive, but not definitive, evidence that progress is being made. Incidence rates are stabilising in those younger than 35 years and the proportionate increase for both in situ and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
185
1
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(208 citation statements)
references
References 18 publications
15
185
1
7
Order By: Relevance
“…Whites and Canada), Israel and Norway (and perhaps very recently in France and Iceland) suggest a recent leveling off or slight decline in melanoma incidence rates, whereas the observed trends reach statistical significance only in Australia (at ages 25-44 years) and Iceland (among women, all ages). This finding, more readily apparent among young persons aged 25-44 years of age, is in accordance with earlier observations of stable incidence trends among young people in Australia (Queensland, 5,15 New South Wales 51 ), Canada, 52 the U.S. 13 and some Northern European countries 3 and may be associated with changing UV radiation exposure patterns following a growing awareness of skin cancer and its risk factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Whites and Canada), Israel and Norway (and perhaps very recently in France and Iceland) suggest a recent leveling off or slight decline in melanoma incidence rates, whereas the observed trends reach statistical significance only in Australia (at ages 25-44 years) and Iceland (among women, all ages). This finding, more readily apparent among young persons aged 25-44 years of age, is in accordance with earlier observations of stable incidence trends among young people in Australia (Queensland, 5,15 New South Wales 51 ), Canada, 52 the U.S. 13 and some Northern European countries 3 and may be associated with changing UV radiation exposure patterns following a growing awareness of skin cancer and its risk factors.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of melanoma has steadily increased over the last 50 years in most fair-skinned populations. [2][3][4][5][6] Such observations have been well documented in Europe 3,[7][8][9][10][11][12] (particularly in the Nordic countries), 2,3 North America, 13,14 Australia and New Zealand, 5,6 where incidence rates remain the highest reported worldwide. Nevertheless, several studies published during the last decade have reported rates in several of these populations as either stabilizing or declining, including a number of Northern and Western European countries, 3 the U.S., 13 Canada, 14 Australia 5,15 and New Zealand.…”
mentioning
confidence: 95%
“…In this age group, incidence in Scotland is now greater in males than in females, a pattern not reported before in the UK. The general pattern worldwide is that in relatively low-incidence countries female exceeds male incidence, but in higher-incidence countries such as Australia, the incidence is either equal, or there is a male preponderance (Coory et al, 2006). Thus, Scotland appears to be moving toward the pattern of a high-incidence country.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous melanoma is a cause of concern for those involved in cancer control in Europe (de Vries et al, 2003;Hemminki et al, 2003;de Vries and Coebergh, 2004), North America (Jemal et al, 2001;Swetter et al, 2005), and Australasia (Martin and Robinson, 2004;Baade and Coory, 2005;Coory et al, 2006). Data from all three continents show a continuing rise in incidence, although in some countries incidence figures may be stabilising in younger females.…”
mentioning
confidence: 99%
“…Queensland, Australia has the highest incidence of melanoma in the world, with 34,000 residents in a population of $4 million people being diagnosed with the disease in the last two decades (Coory et al, 2006). The 5-year survival rate for metastatic malignant melanoma is less than 5% as the tumors are largely refractory to existing therapies (Cummins et al, 2006).…”
Section: Introductionmentioning
confidence: 99%